Analisis Perjudian Online Berdasarkan Pasal 303 KUHP dan UU NO. 11 Tahun 2008 JO. UU NO 19 Tahun 2016 Tentang ITE: Studi Putusan Nomor 1248/PID.B2021 - Tanu, Ericsson; Nurhayani , Nurhayani (VISA: Journal of Vision and Ideas, 2026)
Information technology has shifted gambling from conventional, face-to-face activities into online gambling through websites, applications, and digital platforms. This shift complicates enforcement when electronic conduct is still charged under the general provisions of the Indonesian Criminal Code (KUHP). This research examines the North Jakarta District Court Decision No. 1248/Pid.B/2021/PN Jkt.Utr by linking the court’s reasoning to the principle of lex specialis derogat legi generali and by assessing it from the standpoint of legal certainty. The study applies normative legal research using a statute approach to Article 303 KUHP and Article 27(2) of the ITE Law, as amended by Law No. 19 of 2016, alongside a case approach through analysis of the decision. The findings show that the facts involved electronic elements accounts, online deposits, internet access, and platform use yet the conviction and sentencing relied mainly on Article 303 KUHP. Consequently, lex specialis was not applied optimally and the cybercrime dimension was not adequately captured. From a legal-certainty perspective, this approach may create inconsistent treatment of similar cases and reduce predictability. The paper recommends prioritising Article 27(2) of the ITE Law as the primary basis for online gambling, treating Article 303 KUHP as an alternative, and developing judicial guidelines to standardise practice.